2023
DOI: 10.3390/pr11061776
|View full text |Cite
|
Sign up to set email alerts
|

Study on Multi-Mode Switching Control of Intelligent Suspension under Full Road Section

Abstract: The safety, comfort, and energy feedback of active suspension in a single control mode is mutually restricted. To meet the needs of drivers and passengers for vehicle driving performance under different road conditions, this paper proposes a multi-mode switching control strategy of an intelligent suspension system, aiming at improving the stability and comfort of vehicles under different road conditions. In this paper, the adaptive Kalman filter algorithm with a forgetting factor is used to estimate the road i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Several other studies can also be found in the literature and include control approaches such as the linear quadratic regulator [21][22][23], adaptive sliding control [24], H∞ control [25,26], advanced fuzzy control [27,28], optimal control [15,29] and neural-networkbased methods for tuning [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies can also be found in the literature and include control approaches such as the linear quadratic regulator [21][22][23], adaptive sliding control [24], H∞ control [25,26], advanced fuzzy control [27,28], optimal control [15,29] and neural-networkbased methods for tuning [30,31].…”
Section: Introductionmentioning
confidence: 99%